2002
DOI: 10.1089/10766290260469589
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Antibiotic Resistance inEscherichia coliIsolates Obtained from Healthy Children in Spain

Abstract: Antibiotic resistance and mechanisms involved were studied in Escherichia coli isolates from fecal samples of healthy children. Fifty fecal samples were analyzed, and one colony per sample was recovered and identified by biochemical and molecular tests. Forty-one E. coli isolates were obtained (82%). MIC testing was performed by agar dilution with 18 antibiotics, and the mechanisms of resistance were analyzed. Ampicillin resistance was detected in 24 isolates (58.5%), and blaTEM, blaSHV, and blaOXA type genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 40 publications
3
28
1
3
Order By: Relevance
“…Previous studies have shown that the efflux tetA and tetB are the commonest tetracycline resistance genes generally observed in E. coli [28,29]. The tet genes occurrence are frequent on mobile genetic elements e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the efflux tetA and tetB are the commonest tetracycline resistance genes generally observed in E. coli [28,29]. The tet genes occurrence are frequent on mobile genetic elements e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, tet(A) and tet(B), both of which encode efflux mechanisms, have been identified previously as the most common tetracycline resistance genes in E. coli of both human and animal origin (7,16).…”
Section: Discussionmentioning
confidence: 99%
“…Tetracycline is never given to children, due to its effect on growing bones and teeth (29). Tetracycline is not used to treat E. coli infections in humans, but resistance to tetracycline is still common in E. coli (4,7), which suggests that resistance has been selected by a bystander effect on commensal E. coli, during treatment of other pathogens in humans or animals. Bacterial resistance to tetracycline is most commonly mediated by energy-dependent pumping of tetracycline out of the bacterial cell.…”
mentioning
confidence: 99%
“…In a different study in the United States conducted with cervicovaginal and rectal E. coli isolates they found no differences between antimicrobial susceptibility and resistance rates of these isolates and determined to antimicrobial resistance rate to ampicillin as 39.50% (14). Ampicillin resistance rates of fecal flora E. coli isolates are determined in Germany 16.70% in Serbia 42.00% in Korea 43.70% in Spain 58.50% and in Mexico 100% (15)(16)(17)(18)(19).…”
Section: Yang Et Al (6) In Their Study Made In China Theymentioning
confidence: 97%